Expected goals model with pre-shot movement, Part 4: Variable importance - Novet, A. (2019)
In the last two posts, the authors have looked at the big picture outputs of the xG model for players and teams. Now, let`s zoom in on the model itself to try and understand it better. How is it making its decisions? Which variables provide the most important information and in what way do those variables affect the outcome?